Nordihydroguaiaretic Acid: From Herbal Medicine to Clinical Development for Cancer and Chronic Diseases - Manda, Gina; Rojo, Ana I.; Martínez-Klimova, Elena; Pedraza-Chaverri, José; Cuadrado, Antonio (Frontiers in Pharmacology, 2020)
Nordihydroguaiaretic acid (NDGA) is a phenolic lignan obtained from Larrea tridentata, the creosote bush found in Mexico and USA deserts, that has been used in traditional medicine for the treatment of numerous diseases such as cancer, renal, cardiovascular, immunological and neurological disorders, and even aging. NDGA presents two catechol rings that confer a very potent antioxidant activity by scavenging oxygen free radicals and this may explain part of its therapeutic action. Additional effects include inhibition of lipoxygenases (LOXs) and activation of signaling pathways that impinge on the transcription factor Nuclear Factor Erythroid 2-related Factor (NRF2). On the other hand, the oxidation of the catechols to the corresponding quinones my elicit alterations in proteins and DNA that raise safety concerns. This review describes the current knowledge on NDGA, its targets and side effects, and its synthetic analogs as promising therapeutic agents, highlighting their mechanism of action and clinical projection towards therapy of neurodegenerative, liver and kidney disease, as well as cancer.